Wide QRS complex tachycardia after surgical repair of an isolated atrial septal defect: What is the mechanism?. Issue 2 (22nd February 2021) - Wang, Norman C.
Abstract : Macroreentrant atrial tachycardia within the right atrium is the dominant mechanism in patients with prior surgical repair of atrial septal defects, with dual‐loop circuits much more common than single‐loop circuits. This case highlights the importance of clinical history for predicting arrhythmia mechanisms. Considering prior cardiac surgery may assist in preprocedural preparations and discussions regarding potential risks and benefits of catheter ablation.